Impact of Urban Development on Avian Diversity in Mangalavanam, Kochi - Athul Krishnan S (Calibrating Urban Livability in the Global South, 2024)
This research paper investigates the repercussions of urban development on avian biodiversity within the Mangalavanam Feathered creature Haven found in Kochi, India. The think-about points to get it the relationship between the development of new buildings and the waning populace of feathered creatures within the haven. The inquiry highlights the noteworthy decrease in winged creature species abundance and wealth as a result of expanded urbanization. The discoveries emphasize the critical requirement for feasible urban arranging and preservation endeavors to moderate the advanced misfortune of avian differing qualities in this environmentally pivotal living space.